2019
DOI: 10.1038/s41598-019-52405-0
|View full text |Cite
|
Sign up to set email alerts
|

Inhibiting the LPS-induced enhancement of mEPSC frequency in superficial dorsal horn neurons may serve as an electrophysiological model for alleviating pain

Abstract: Pain is a major primary health care problem. Emerging studies show that inhibition of spinal microglial activation reduces pain. However, the precise mechanisms by which microglial activation contributes to nociceptive synaptic transmission remain unclear. In this study, we measured spontaneous synaptic activity of miniature excitatory postsynaptic currents (mEPSCs) in rat spinal cord superficial dorsal horn (SDH, laminae I and II) neurons. Lipopolysaccharide (LPS) and adenosine triphosphate (ATP) increased th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 55 publications
(95 reference statements)
1
8
0
Order By: Relevance
“…The dose of oxytocin was chosen from previous studies of intrathecal oxytocin injections that inhibit nociception in a range of 0.1-10 nmol (Chow et al, 2016;. LPS concentration was determined from earlier reports showing that it induces increases in the spontaneous electrical activity of neurons in the spinal cord (Yang et al, 2019). In addition, other authors demonstrated that LPS induces the activation of the glia and differentiation of these cells to a proinflammatory phenotype that generates nociception (Inceoglu et al, 2006;Morioka et al, 2019;Qi, Zhao, Li, Liang & Yu, 2020).…”
Section: Intrathecal Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The dose of oxytocin was chosen from previous studies of intrathecal oxytocin injections that inhibit nociception in a range of 0.1-10 nmol (Chow et al, 2016;. LPS concentration was determined from earlier reports showing that it induces increases in the spontaneous electrical activity of neurons in the spinal cord (Yang et al, 2019). In addition, other authors demonstrated that LPS induces the activation of the glia and differentiation of these cells to a proinflammatory phenotype that generates nociception (Inceoglu et al, 2006;Morioka et al, 2019;Qi, Zhao, Li, Liang & Yu, 2020).…”
Section: Intrathecal Treatmentmentioning
confidence: 99%
“…LPS-intrathecal injection allows localized activation of glial populations. This LPS can be administered intrathecally, systemically or peripherally local and produces hypersensitivity in the short and long term (Cahill, Dray & Coderre, 2003;Moss et al, 2007;Qi et al, 2020;Yang et al, 2019).…”
Section: Induction Of Mechanical Hypersensitivity By Lpsmentioning
confidence: 99%
“…The innate behaviors of LPS-induce mice in automated home-cage monitoring should be carefully interpreted as behavioral pain since LPS was administered intraperitoneally. Although intraperitoneal administration of LPS has been devised in several pain models, such as sepsis-associated pain, musculoskeletal pain, and visceral pain [11,[18][19][20]35], the intraperitoneal administration of LPS can cause a systemic immune response leading to the development of sickness behaviors. Sickness behaviors produced by intraperitoneal administration of LPS include fatigue, depressive-like behavior, feeding behavior, anxiolytic-like behavior, changes in sleep-wake and feeding behaviors, weight loss, fever, and pain-like behaviors [8][9][10][11][12][13].…”
Section: Plos Onementioning
confidence: 99%
“…At the mechanistic levels both sickness and painlike behaviors are associated with increased pro-inflammatory mediators [8,17]. Therefore, the use of endotoxin has been recently introduced as a model for the study of inflammatory pain in both animals and humans [18][19][20][21][22][23][24][25]. The administration of LPS produces a significant expression of proinflammatory mediators, like cytokines, chemokines, cyclooxygenase-2 (COX-2), and nitric oxide through activation of toll-like receptor 4 (TLR4) via modulating immune cells [26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…Two possible pathways are indicated for this effect: the activation of sympathetic nerve fibers to intensify the displacement of opioid-containing cells and the reduction of COX-2 activity in the hypothalamus-pituitary-adrenal axis, a major neuroendocrine system, which consecutively reduces the production of prostaglandin [49]. Furthermore, increasing evidence suggests that neuropathic pain leads in microglia activation through ATP receptors [50]. In turn, activated microglia release ATP and cytokines, triggering astrocyte activation and contributing to neuroinflammation [51].…”
Section: Possible Mechanisms Of the Analgesic And Neuroprotective Effmentioning
confidence: 99%